Smoking behaviours and attitudes among male restaurant workers in Boston's Chinatown: a pilot study. (1st June 2002) - Averbach, A R; Lam, D; Lam, L-P; Sharfstein, J; Cohen, B; Koh, H
Abstract : Objective: Asian American immigrants experience high rates of cigarette smoking. A community based survey was conducted to understand the smoking behaviours, knowledge, and attitudes of restaurant workers in Boston's Chinatown. Design: Cross sectional survey in Chinese of a convenience sample of 54 restaurant workers recruited through extensive outreach activities. Results: All 54 of the workers were male immigrants. 45 (83.3%) reported smoking cigarettes regularly, and the remaining nine were former smokers. 36 of the smokers (80.0%) started smoking before entering the USA. The workers were aware that cigarettes are addictive (98.1%), cause lung cancer (79.6%), and lead to heart disease (64.8%). However, a substantial number reported that smoking was relaxing (75.9%) and enhanced concentration (66.7%). Nearly half believed low tar and low nicotine cigarettes to be safer than standard brands. The vast majority of workers believed that smoking was not socially acceptable for women. Smokers reported they received information on quitting most commonly from friends (60%), newspapers (53.5%), and television (44.4%). The restaurant workers most often saw advertising against smoking in Chinese newspapers (63%). Conclusion: Despite high rates of smoking, Chinese American restaurant workers were generally aware of the health risks and were interested in quitting. Community based research can set the stage for targeted public health efforts to reduce smoking in immigrant communities.